Hemostatic biomarkers in cancer progression. Issue 164 (April 2018) - Falanga, Anna; Marchetti, Marina
Abstract: Malignant disease is characterized by a hemostatic imbalance, usually shifted towards a procoagulant direction, and a high incidence of thrombotic complications. The mechanisms of hemostasis that are critically involved in thrombosis are also implicated in tumor progression, angiogenesis, and metastatic spread. As there is a close relationship between cancer and the clotting system, circulating biomarkers of activation of various hemostasis compartments (i.e. coagulation, fibrinolysis, platelets, endothelium, and other blood cells) have been extensively studied to predict cancer outcomes along with predicting the thrombotic risk. In this review, we will summarize the results of published studies and will focus on ongoing research and future directions of clotting activation bioproducts as biomarkers of cancer disease and progression. Highlights: Mechanisms of hemostasis are implicated in tumor progression Significant relationships of hemostatic biomarkers with different tumor outcomes have been reported Prospective clinical trials are needed for the clinical validation of the majority of hemostatic biomarkers.